Role of mini-scleral lens in mucous membrane pemphigoid - Kumar, Mukesh (Indian J Ophthalmol, 2017)
This study aims to report the use of mini-scleral contact lens in the management of mucous membrane pemphigoid (MMP) with persistent epithelial defects. A 68-year-old male with a history of ocular pain and declining visual acuity was referred to our clinic with a diagnosis of MMP. His corrected distance visual acuity (CDVA) was 20/200 in the right eye and 20/100 in the left eye. Despite being on lubricants, topical steroids and intravenous cyclophosphamide, the patient developed persistent corneal epithelial defects in both eyes. He was then given a trial of mini-scleral lenses. Within 4 weeks, corneal epithelial defects healed, and at 6 months, the CDVA had improved to 20/50 in the right eye and 20/40 in the left eye. By improving the corneal surface integrity and visual function, mini-scleral lenses can play a role in the visual rehabilitation of patients with MMP.